DEVELOPMENT OF CORRUGATED SHELL STRUCTURE AND STUDY OF ITS EFFECT ON THERMOSET COMPOSITE SHEET - MD NADZIR, MUHAMMAD FAISAL (IRC, 2018)

(untitled)
Corrugations are believed to enhance the mechanical properties of a shell structure, but this theory still requires further validation through experimental work on various materials. Even though numerous studies have been conducted on corrugated shell structures, the effect of corrugations on thermoset composite sheets, in terms of flexibility, remains unexplored. This study focuses specifically on thermoset composite sheets which are epoxy reinforced with s-type fiberglass and the mechanical properties are experimentally determined with different corrugated profiles. Corrugated profiles were studied in this project which is the damped sin wave and a vibration profile. A few simulations are run to obtain useful data about the behavior of the corrugated structure. The corrugated profiles were then designed in SOLIDWORKS, which was used to fabricate the mold required for corrugated thermoset composite preparation. A compression molding machine was used to form the corrugations on the composite material as it can deliver high pressure and temperature to cure the laminate. In this study, the compression molding process was carried out under constant parameters: temperature, pressure and holding time. Result obtained from vibration testing of the thermoset composite sheets compared with the flat sample to determine the effect of corrugations.